Comparative morpho-anatomical studies of Hoya incrassata and Hoya soligamiana (Apocynaceae) from Mount Hamiguitan, Philippines - D.S. Salas; E.B. Sinamban; D.P. Buenavista (Ruhuna Journal of Science, 2018)
This study compared the morpho-anatomical characters of two horticulturally important hoyas endemic to the Philippines viz., Hoya incrassata and Hoya soligamiana. Fresh cuttings were used for morphological and anatomical measurements. Free hand sections were taken from leaves, shoots and roots for determination of structural differences. Leaf pigments were cleared to observe the venation and stomatal arrangement. The results showed that hoyas differ in their leaf shape and texture, flower colour, and the inflorescence shape and position. H. soligamiana has glabrous lanceolate leaves, whitish to creamy petals, purplish to pink inner and outer coronal lobes, and whitish to pink fused sepals. H. incrassata has coriaceous lance-ovate leaves, whitish to yellowish fused petals, yellow inner coronal lobes, reddish to orange outer coronal lobes, and fused sepals. The measured anatomical traits in the cross sections of roots and stems of the two Hoya species did not differ with the exception of stomatal types and arrangement in the leaves. The pigment clearing of the leaves showed that H. incrassata has sunken cyclocytic stomata while H. soligamiana has actinocytic stomata. Morpho-anatomical information provides taxonomic value for identifying and classifying the two Hoya species.